Health Benefits of (Poly)phenols from Cherries: A Review of Clinical Trials - Alessandro Colletti; Giancarlo Cravotto; Atanasio De Meo; Marzia Pellizzato; Enzo Luigi Riccardi; Marco Marchetti (Nutraceuticals)
Cherries are well known to be a rich source of (poly)phenols, especially anthocyanins, with exhibited antioxidant and anti-inflammatory properties. The aim of this review is to describe the effects of cherry extract observed in clinical trials and the respective tolerability indications, highlighting the differences in efficacy depending on the type of extract, cherry, formulation, and dosage used. In particular, the supplementation of standardized tart cherry extracts has been shown to improve different markers of human health, exercise performance, and quality of sleep. Most clinical studies conducted to date have reported the total (poly)phenol and anthocyanin doses administered that were contained in cherry extracts, which ranged from 143 to 2140 mg/day and 15 to 547 mg/day, respectively, as well as the duration of treatments, which ranged from acute supplementation to 84 days. Although cherry extracts are currently prescribed as dietary supplements in several areas of medicine, further investigations of the mechanisms of action and long-term randomized clinical trials (RCTs) are required in order to validate the efficacy and safety of clinical applications. In addition, a real challenge for the next few years is the standardization of cherry’s (poly)phenolic fractions. In this context, the optimization of the extraction procedure and downstream processing represents a key point in reliable active guiding principles for the formulation of food supplements. In fact, due to the different extraction methods of cherries, the relative efficacy is closely related to the specific (poly)phenol profile obtained, which cannot be extrapolated from the literature. Future research should include an analysis reporting the total (poly)phenol content and the specific analytical methods used to quantify total and individual anthocyanin contents.